Tabassum Kashmiri as A Literary Historian - Siddiqa, Tahira; Naveed, Muhammad (sourcecoder, 2022)
This research article analyzes Dr. Tabassum Kashmiri's Urdu Adab ki Tarikh in the context of other histories of Urdu. His modern trends, unique style, and new ideas have been identified. This has led to an attempt to figure out his position as a literary historian